A geochemical study of the winonaites: Evidence for limited partial melting and constraints on the precursor composition - Hunt, A.; Benedix, G.; Hammond, S.; Bland, Phil; Rehkämper, M.; Kreissig, K.; Strekopytov, S. (Pergamon, 2017)
The winonaites are primitive achondrites which are associated with the IAB iron meteorites. Textural evidence implies heating to at least the Fe, Ni–FeS cotectic, but previous geochemical studies are ambiguous about the extent of silicate melting in these samples. Oxygen isotope evidence indicates that the precursor material may be related to the carbonaceous chondrites. Here we analysed a suite of winonaites for modal mineralogy and bulk major- and trace-element chemistry in order to assess the extent of thermal processing as well as constrain the precursor composition of the winonaite-IAB parent asteroid. Modal mineralogy and geochemical data are presented for eight winonaites. Textural analysis reveals that, for our sub-set of samples, all except the most primitive winonaite (Northwest Africa 1463) reached the Fe, Ni–FeS cotectic. However, only one (Tierra Blanca) shows geochemical evidence for silicate melting processes. Tierra Blanca is interpreted as a residue of small-degree silicate melting. Our sample of Winona shows geochemical evidence for extensive terrestrial weathering. All other winonaites studied here (Fortuna, Queen Alexander Range 94535, Hammadah al Hamra 193, Pontlyfni and NWA 1463) have chondritic major-element ratios and flat CI-normalised bulk rare-earth element patterns, suggesting that most of the winonaites did not reach the silicate melting temperature. The majority of winonaites were therefore heated to a narrow temperature range of between ~1220 (the Fe, Ni–FeS cotectic temperature) and ~1370 K (the basaltic partial melting temperature). Silicate inclusions in the IAB irons demonstrate partial melting did occur in some parts of the parent body (Ruzicka and Hutson, 2010), thereby implying heterogeneous heat distribution within this asteroid. Together, this indicates that melting was the result of internal heating by short-lived radionuclides. The brecciated nature of the winonaites suggests that the parent body was later disrupted by a catastrophic impact, which allowed the preservation of the largely unmelted winonaites. Despite major-element similarities to both ordinary and enstatite chondrites, trace-element analysis suggests the winonaite parent body had a carbonaceous chondrite-like precursor composition. The parent body of the winonaites was volatile-depleted relative to CI, but enriched compared to the other carbonaceous classes. The closest match are the CM chondrites; however, the specific precursor is not sampled in current meteorite collections.